2022
DOI: 10.3390/plants11030263
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Humic Acid Synergistically Increase Salt Tolerance and Nutrient Uptake in Contrasting Wheat Genotypes through Ionic Homeostasis and Activation of Antioxidant Enzymes

Abstract: Salinity limits the growth and nutrient uptake in crop species. Studies show that both potassium (K) and humic acid (HA) improved plant tolerance to salinity. However, the interactive effect of K and HA on plant tolerance to salinity stress remains unknown. This pot study examined the effect of application of K (0, 5 or 10 mM) and HA (0 or 2 g kg−1), alone or in combination, on the growth and physiology under salinity (100 mM NaCl) in two wheat genotypes (SARC 1, salt tolerant; and SARC 5, salt sensitive). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 56 publications
(106 reference statements)
4
28
0
Order By: Relevance
“…Application of humic acid under saline conditions reduces the generation of ROS in common bean ( Phaseolus vulgaris L) by triggering the activities of antioxidant enzymes SOD, CAT and POD resulting in least MD and less electrolyte leakage ( Aydin et al,2012 ). Similarly, Abbas et al (2022) observed improvement in wheat tolerance against drought and salinity under humic acid application due to initiation of numerous physiological and biochemical activities, like enhanced Gs, and activation of the antioxidant enzymes such as CAT, POD and SOD to mitigate the hazards of ROS. In complement to their findings, current study reported consistent increase in the activities of antioxidant enzymes in all mungbean genotypes under both drought and salinity stresses due to application of humic acids ( Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Application of humic acid under saline conditions reduces the generation of ROS in common bean ( Phaseolus vulgaris L) by triggering the activities of antioxidant enzymes SOD, CAT and POD resulting in least MD and less electrolyte leakage ( Aydin et al,2012 ). Similarly, Abbas et al (2022) observed improvement in wheat tolerance against drought and salinity under humic acid application due to initiation of numerous physiological and biochemical activities, like enhanced Gs, and activation of the antioxidant enzymes such as CAT, POD and SOD to mitigate the hazards of ROS. In complement to their findings, current study reported consistent increase in the activities of antioxidant enzymes in all mungbean genotypes under both drought and salinity stresses due to application of humic acids ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Due to stress, the activities of various antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) are inhibited, hence increasing level of ROS leads to membrane damage (MD) and programmed cell death ( Apel and Hirt, 2004 , Hasanuzzaman et al, 2012 , Nair et al, 2012 , Nair et al, 2019 ). Humic acid improves crop tolerance against drought and salinity due to activation of different biochemical and physiological activities, for instance improved stomatal conductance, and activation of the antioxidant enzymes such as SOD, CAT and POD to undermine the hazards of ROS ( Abbas et al, 2022 ). It has tendency to reduce peroxidation and enhance the homeostatic protein contents by accelerating the uptake of essential nutrients, particularly when soil conditions are marginal ( Dinçsoy and Sönmez, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ghulam et al, studied the influence of HA on salt tolerance and nutrient uptake in wheat. They found out that a combined application of K and HA was promising for increasing wheat salt tolerance and nutrient uptake [ 29 ]. As both studies show very different results and worked with other crops than duckweed, it is difficult to make any concrete conclusions other than a possible indication that duckweed might behave like wheat and have higher salt tolerance in the presence of humic substances.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, applying humic acid to plants allows the plant to cope with environmental stress. For example, the co-application of K and humic acid allows salt-stressed salt-tolerant wheat to shoot dry matter and nutrients (K, Fe, Zn) accumulated as non-stressed ones (Abbas et al, 2022). In addition, the co-application of K and humic acid reduced the Na accumulation in saltstressed wheat plants significantly in both root and shoot (Abbas et al, 2022).…”
Section: Effect Of Humic Acid On Plantmentioning
confidence: 99%